Resistance Assessment for Oxathiapiprolin in Phytophthora capsici and the Detection of a Point Mutation (G769W) in PcORP1 that Confers Resistance - Miao, Jianqiang; Cai, Meng; Dong, Xue; Liu, Li; Lin, Dong; Zhang, Can; Pang, Zhili; Liu, Xili (Frontiers in Microbiology, 2016)
The potential for oxathiapiprolin resistance in Phytophthora capsici was evaluated. The baseline sensitivities of 175 isolates to oxathiapiprolin were initially determinated and found to conform to a unimodal curve with a mean EC50 value of 5.61×10-4 μg/ml. Twelve stable oxathiapiprolin-resistant mutants were generated by fungicide adaption in two sensitive isolates, LP3 and HNJZ10. The fitness of the LP3-mutants was found to be similar to or better than that of the parental isolate LP3, while the HNJZ10-mutants were found to have lost the capacity to produce zoospores. Taken together these results suggest that the risk of P. capsici developing resistance to oxathiapiprolin is moderate. Comparison of the PcORP1 genes in the LP3-mutants and wild-type parental isolate, which encode the target protein of oxathiapiprolin, revealed that a heterozygous mutation caused the amino acid substitution G769W. Transformation and expression of the mutated PcORP1-769W allele in the sensitive wild-type isolate BYA5 confirmed that the mutation in PcORP1 was responsible for the observed oxathiapiprolin resistance. Finally diagnostic tests including As-PCR and CAPs were developed to detect the oxathiapiprolin resistance resulting from the G769W point mutation in field populations of P. capsici.